História, cinema e governos autoritários : aula-oficina sobre perseguições as minorias no tempo presente - Tomazela, Fernanda Santos (2024)
This work intendsto relate the teaching of history, the use of cinema and the holding of classesworkshops. Given the global political scenario in which far-right authoritarian governments have advanced in recent years, it is considered essential to address this issue as we believe in the need to understand this new political phenomenon of the 21st century and defend the principles that govern democratic societies. It is understood that cinema can be used to reflect on a topic. Thus, our intention isto use the film V for Vendetta (2006) as a historicalsources in the historical learning process of young students. In it, we intend to select scenes that make it possible to discuss the topic of minorities. Based on cinematographic production, the intention isto dialogue with other sources of research for teaching history. Comparing different sources and considering students as active subjects in the training process, this work aims to present the following product: Workshop Class to work with scenes from the film to reflect on the persecution of minorities by authoritarian regimes. It is hoped, therefore, to encourage reflection on the practices of authoritarian governments.